(untitled) (Docentes 2.0 Journal, 2025)
The COVID-19 pandemic caused an unprecedented disruption in educational systems worldwide. This situation accelerated the incorporation of information and communication technologies (ICTs) as a central axis of pedagogical processes. The objective of this research was to determine the relationship between the use of ICTs and the significant improvement in pedagogical practice at the "San Juan de la Virgen" Educational Institution in Tumbes during the 2022-2023 post-pandemic period. This research was conducted within the positivist paradigm, using the hypothetical-deductive method, a quantitative approach, a non-experimental correlational design, and a cross-sectional approach. A validated questionnaire was administered to 70 participants (23 teachers and 47 students), evaluating dimensions such as technological tools, connectivity, and teaching competencies. The results revealed that 39% of teachers used ICTs at a high level, and 74% demonstrated high-quality pedagogical practices, evidencing a positive correlation. However, critical gaps persist: 59% of teachers used ICTs moderately, and limited access to infrastructure (26% with medium connectivity) hindered their optimal impact. These findings support the potential of ICTs as learning facilitators, highlighting the need for comprehensive policies that combine technological access, ongoing teacher training, and contextual adaptation. It is concluded that, despite limitations, the strategic integration of ICTs can transform post-pandemic challenges into opportunities for more innovative and inclusive education in resource-limited contexts.